Pengaruh Kinerja Bidan dalam Melakukan Diteksi Dini Bayi Berat Lahir Rendah (BBLR) - Lisvi Ulita; Irwan Saputra; Nurjannah Nurjannah; Asnawi Abdullah; Aulina Adami (LPPM Hang Tuah Pekanbaru, 2023)
Obstetrics services are an intensive part of health activities focused on maternal, newborn, and child health to realize meaningful family health. Maternal and child health is a national agenda that deserves top priority because it determines the quality of human resources for the next generation. This research method is analytical with a cross-sectional study design. The study sample consisted of 88 midwives. Data analysis was performed using regression analysis and the Results of bivariate. The results of the bivariate test found a relationship between knowledge (p=0.003), motivation (p=0.033), and leadership (p=0.000) with obstetric performance. Furthermore, although there is no relationship between attitudes (p=182) and obstetric performance, the variables of supervision, reward, and training show satisfactory results. The results of the multivariate analysis show that leadership is the most dominant factor in determining obstetric performance, with a p-value of 0.000 and OR. 180. Request the Aceh Besar Health Office to increase supervision not only from the supervising coordinating midwife but also from the abscess and the health office.